2014
DOI: 10.1007/s12032-014-0394-9
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-inducible factor 1-alpha up-regulates the expression of phospholipase D2 in colon cancer cells under hypoxic conditions

Abstract: Hypoxia is a common characteristic of solid tumors. Recent studies confirmed that phospholipase D2 (PLD2) plays significant roles in cancer progression. In this study, correlation between the expression of PLD2 and the change in the protein level of hypoxia-inducible factor 1-alpha (HIF1-α) was studied. Thirty human colon cancer tissues were examined for the expression of HIF1-α and PLD2 protein, and mRNA levels. SW480 and SW620 cells were exposed to normoxia (20 %) or hypoxia (<1 %). HIF1-α and PLD2 protein, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Interestingly, it has been reported that HIF-1α upregulates PLD2 at the transcriptional level under hypoxic conditions, although it is unknown how HIF-1α induces PLD2 expression. 25 Thus, PLD and HIF-1α might affect their biological functions via reciprocal regulation. Because PLD mediates mitogenic and oncogenic signaling 1 and HIF-1α is a central initiator of angiogenic activity in tumors, it was suggested that PLD might utilize the HIF-1α-VEGF pathway as a tumorigenic effector.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, it has been reported that HIF-1α upregulates PLD2 at the transcriptional level under hypoxic conditions, although it is unknown how HIF-1α induces PLD2 expression. 25 Thus, PLD and HIF-1α might affect their biological functions via reciprocal regulation. Because PLD mediates mitogenic and oncogenic signaling 1 and HIF-1α is a central initiator of angiogenic activity in tumors, it was suggested that PLD might utilize the HIF-1α-VEGF pathway as a tumorigenic effector.…”
Section: Discussionmentioning
confidence: 99%
“… 24 Moreover, HIF-1α upregulates PLD2 expression in response to hypoxic stress. 25 Thus, PLD and HIF-1α might be involved in tumor progression via positive feedback regulation. Interestingly, we found that PLD1 protein itself mediates efficient degradation of HIF-1α by coordinating the dynamic assembly of PHD-HIF-1α-VHL.…”
Section: Introductionmentioning
confidence: 99%
“…Immunohistochemical staining of 30 human colon cancer samples revealed a high level of correlation between Hif1-␣ and PLD2 ( 79 ). Moreover, Hif1-␣ and PLD2 expression levels are much higher in colon cancer tissues than in normal colon tissues ( P < 0.01) ( 79 ), and under function. Nonetheless, PLD4 clearly has important functional roles.…”
Section: Pld3mentioning
confidence: 94%
“…Although the overall expression levels of PLD2 may vary in tumors, there is a signifi cant correlation between PLD2 expression level and tumor size ( P < 0.05), as well as with survival of patients with colorectal carcinoma ( P < 0.05) ( 78 ). Immunohistochemical staining of 30 human colon cancer samples revealed a high level of correlation between Hif1-␣ and PLD2 ( 79 ). Moreover, Hif1-␣ and PLD2 expression levels are much higher in colon cancer tissues than in normal colon tissues ( P < 0.01) ( 79 ), and under function.…”
Section: Pld3mentioning
confidence: 98%
“…Overexpression of HIF-1α in tumor cells is closely connected with increased resistance to radio-and chemotherapies, increased risk of metastasis, more aggressive phenotype, and strengthened immune suppression [59]. HIFs are also involved in COX2/mPGES-1/PGE2, WNT, and STAT3 signaling pathways correlating with CRC carcinogenesis [25,60,61], and implicated in CRC development and metastasis [62][63][64][65][66][67]. But the conclusions above were acquired under continuous hypoxia condition.…”
Section: Gut Microbiota Of Osas Could Activate Tumorigenesis Pathwaymentioning
confidence: 99%